Effects of sodium hexametaphosphate microparticles or nanoparticles on the growth of saliva-derived microcosm biofilms - Sampaio, Caio [UNESP]; Deng, Dongmei; Exterkate, Rob; Zen, Igor [UNESP]; Hosida, Thayse Yumi [UNESP]; Monteiro, Douglas Roberto [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP] (Springer Nature, 2022)
Objectives: This study evaluated the effects of sodium hexametaphosphate microparticles (HMPmicro) or nanoparticles (HMPnano) on the growth of saliva-derived microcosm biofilms Materials and methods: Saliva-derived biofilms were formed on glass coverslips for 24 h. Thereafter, Streptococcus mutans (C180-2) was incorporated or not into the biofilms. From that time point onwards, solutions containing 0.2% HMPmicro or HMPnano, combined or not with 220 ppm F, were constantly present in the culture medium. In addition, 220 ppm F alone (220F) and McBain medium without any compound were also tested as positive and negative controls (CTL), respectively. After 96 h, the biofilms were plated on anaerobic blood agar or sucrose agar bacitracin for total and S. mutans CFU-counting, respectively. Biofilms’ lactic acid production was analysed spectrophotometrically. Data were submitted to ANOVA or Kruskal-Wallis’ tests, followed by Student-Newman-Keuls’ test (p<0.05; n=12). Results: HMPmicro or HMPnano led to significantly lower lactic acid production, and significant reductions in total CFU-counting in microcosm biofilms, supplemented or not with S. mutans, in comparison to both controls, with significant differences between 220F and CTL. No significant differences were observed among the groups treated with HMPmicro or HMPnano (with or without F). The same trend was seen for S. mutans CFU-counting, in biofilms supplemented with S. mutans. Conclusions: HMP significantly reduced total and S. mutans CFU counts, as well as lactic acid production by saliva-derived microcosm biofilms. Clinical relevance: These findings in saliva-derived microcosm biofilms suggest that HMP stands as a promising alternative for the control of cariogenic biofilms.
Keywords: Biofilms; Fluorides; Nanotechnology; Phosphates